Strategies for developing long-lasting therapeutic nucleic acid aptamer targeting circulating protein: The present and the future - Zhang, Yihao; Zhang, Huarui; Chan, Daniel Wing Ho; Ma, Yuan; Lu, Aiping; Yu, Sifan; Zhang, Baoting; Zhang, Ge (Frontiers in Cell and Developmental Biology, 2022)
Aptamers are short, single-stranded DNA or RNA oligonucleotide sequences that can bind specific targets. The molecular weight of aptamers (<20 kDa) is lower than the renal filtration threshold (30~50 kDa), resulting in very short half-lives in vivo, which limit their druggability. The development of long-lasting modification approaches for aptamers can help address the druggability bottleneck of aptamers. This review summarized two distinct kinds of long-lasting modification approaches for aptamers, including macromolecular modification and low-molecular-weight modification. Though it is a current approach to extend the half-life of aptamers, the macromolecular modification approach could limit the space for the dosage increases, thus causing potential compliance concerns due to large molecular weight. As for the other modification approach, the low-molecular-weight modification approach, which uses low molecular weight coupling agents (LMWCAs) to modify aptamers, could greatly increase the proportion of aptamer moiety. However, some LMWCAs could bind to other proteins, causing a decrease in the drug amounts in blood circulation. Given these issues, the outlook for the next generation of long-lasting modification approaches was proposed at the end, including improving the administration method to increase dosage for aptamer drugs modified by macromolecule and developing Artificial intelligence (AI)-based strategies for optimization of LMWCAs.